Women's Footprint in Anti-Doping Sciences: A Bibliometric Approach to Research Impact - Anna Kiss; Anna Kiss; Zoltán Lakner; Zoltán Lakner; Sándor Soós; Sándor Soós; Andrea Petróczi; Andrea Petróczi; Andrea Petróczi (Frontiers in Sports and Active Living, 2022)
Bibliometrics, via the exploitation of large-scale publication data, is a facile approach to explore gender-related trends, especially gender equality in academic publishing and authorship. For the first time, this study aims to investigate the gender-related trends in anti-doping sciences to (1) explore the relational structure of gender aspects of authorial, topical, and methodological features, (2) give recognition to women's contribution to anti-doping research, and (3) identify unique “gendered” potentials for advancing anti-doping research. To deliver on these aims, we employed bibliometric tools to publication records in anti-doping. After constructing a database containing academic publications on any aspect of anti-doping with at least one woman among the authors, we applied state-of-the-art methods from bibliometric science mapping and network analysis. The Lotka distribution model showed that the anti-doping research is a closed community with only 70 authors appearing more than once. Male authors being the majority (66.2%), women are under-represented in this field. The most important authorship position in the academic articles is mainly occupied by men, publications with male corresponding authors were in 774 out of 991 anti-doping related papers. The close connection of the top twenty most influential authors, men and women, to the World Anti-Doping Agency in some professional capacity suggest that the Agency have an influence on the anti-doping research beyond directly providing funding. In terms of geographical regions, publications with female authors were dominated anti-doping research in Italy, Romania, and Spain. In research networks to date, women have outperformed male authors in information centrality, which means that women in anti-doping research have had higher level of control over the information flow in the field than their male counterparts. The results of this study confirm the potential of bibliometric approach in the identification of emerging research topics and quantifying gender differentiation in the field of anti-doping. Due to their higher information centrality, women are better positioned for problem-focused multidisciplinary research both within anti-doping community, and with researchers in cognate fields. Bibliometric analyses have proved to be a powerful tool for monitoring and advancing anti-doping research impact via identifying new avenues for multidisciplinary work, better gender representation, and diversity.